The predictive validity of Hammersmith Infant Neurological Examination versus prechtl’s general movement assessment with the Motor optimality score on gross motor outcomes in high-risk infants at 12-15 months corrected age : a descriptive study - Jansen van Rensburg, Emma Anita (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScPhysio)--Stellenbosch University, 2022.